Goat-Soy Milk Kefir Increase Nitric Oxide Bioavailability by Increasing Endothelial Nitric Oxide Synthase (eNOS) Gene Expression in Diabetic rats - Muntafiah, Alfi; ., Nurliyani; ., Sunarti (Progress in Nutrition, 2018)
Objective: Hyperglycemia-stimulated oxidative stress in diabetes mellitus impairs gene expression and activity of endothelial nitric oxide synthase (eNOS). Goat-soy milk kefir has potential to reduce hyperglycemia. This study is to investigate the benefit of kefir from goat and soy milk on eNOS gene expression and nitric oxide (NO) levels. Methods: Twenty five male Wistar rats were grouped as: 1) normal rats; 2) diabetic rats; 3) diabetic rats + goat milk kefir; 4) diabetic rats + combination of goat-soy milk kefir; 5) diabetic rats + soy milk kefir. After kefir intervention for 4 weeks, eNOS gene expression was determined using q-PCR and NO levels was analyzed by ELISA methods. Results: There were significantly differences of the NO levels among group after intervention of kefir for 4 weeks, and the highest NO level was found the diabetic rats with combination of goat-soy milk kefir (p